2011
DOI: 10.1002/jso.22085
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic variables predicting tumor response to neoadjuvant chemotherapy in patients with locally advanced gastric cancer

Abstract: This study suggests that both tumor differentiation and tumor size is the most important clinical predicator of pathologic tumor response, it may be of benefit in the selection of treatment options in locally advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
5
26
1
Order By: Relevance
“…To date, several studies have investigated efficient predictive markers for treatment response. One study reported that tumor differentiation and tumor size could be used as a clinical predicator of pathologic tumor response to neoadjuvant chemotherapy in patients with locally advanced gastric cancer [26]. Gene methylation status was also reported as a predicator of chemotherapy response in gastric cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have investigated efficient predictive markers for treatment response. One study reported that tumor differentiation and tumor size could be used as a clinical predicator of pathologic tumor response to neoadjuvant chemotherapy in patients with locally advanced gastric cancer [26]. Gene methylation status was also reported as a predicator of chemotherapy response in gastric cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…51 A study come from China also suggested that both tumor size and tumor differentiation is the most important clinical predicator of pathologic tumor response. 52 Studies have indicated that lymph nodal status remains one of the most prognostic factors in patients with resected gastric cancer. 53,54 Therefore, the insufficient lymph node dissection for the node-positive cases increases the potential risk of postoperative cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it has been perceived that responders have a significantly better outcome since 1999[23]. Despite the fact that only a limited number of studies presented conflicting result[20][24][25], this conception was further confirmed by several subsequent studies[26][27][28][29]. Taken together, tumor response to NAC could be served as an independent prognostic factor for better prognosis (Figure 2).…”
Section: Histopathological Assessmentmentioning
confidence: 83%
“…Another study suggested TNM staging, histological type, tumor location, sex and age were correlated with histopathological response[27], however, the tumor regression related factors were not fully investigated in this study. Our previous retrospective study of 108 LAGC patients revealed that both tumor size and tumor differentiation were independent predictive marker for NAC responders, who were with better overall survival[28]. Interestingly, based on our updated database, a hypothesis-generating study found serum low-density lipoprotein measurement is useful in predicting chemosensitivity, higher low-density lipoprotein is statistically significant with histopathological response in LAGC patients undergoing NAC[42].…”
Section: Clinicopathological Variables (Summarized In Table 3)mentioning
confidence: 97%
See 1 more Smart Citation